Alih Fungsi Lahan dari Perkebunan Menjadi Lahan Perumahan Di Kota Pangkalpinang - Natasya, Aprilia; Aprillia, Donna Ardila; Agustina, Selli (Indonesian Democracy Research Center, 2022)
Land resources are natural resources that are very important and are considered for human survival. Where land is needed in every human activity, such as for agriculture, residential areas. In Indonesia itself, it has the largest population so that every year the number of population increases causes land conversion to occur. Land conversion, also known as land conversion, is a change in the function of part or all of a land area from its main function to another and has an impact on social conditions and changes in society. The purpose of this research is to see or find out based on how the dynamics that occur in the conversion of land from plantation land to residential areas or land plots and also to find out what factors lead to the conversion of community-owned plantation land and now developing into a residential residential area, as well as seeing what factors are supporting and inhibiting in the transition of land conversion which was originally community-owned plantation land is now developing into a residential residential area in the Kampak area, Gerunggang District, Tua Tunu Village. The method used in this study uses field research that is descriptive qualitative in nature. In this study, the presentation model was carried out by describing an object under study with qualitative statements. This research uses the theoretical study of Access Theory (according to Peluso and Ribot 2003) as a skill to benefit from (the ability to benefit from something. The factors that led to land conversion from plantation land to residential areas, include internal and external factors. The main factor causing this land conversion is due to the economic demands of the Tua Tunu community as landowners, so they sell their plantation-owned land to pay for their children's education, to meet their daily needs, in addition to that, the land they sell is for financial needs. life is like leaving for Umrah or Hajj. Many other supporting factors are also related to the conversion of this land function due to the increasing population growth factor. Land is also strategic for being used as a residential area because the geographical location of the area in this residential area is very easy to reach or access, and this area is also very fast in determining its development.